Covid-19 vaccination and monsoon season / Shahrul Amri Ab Wahab and Syazliana Kasim - Ab Wahab, Shahrul Amri; Kasim, Syazliana (UiTM Cawangan Negeri Sembilan Kampus Seremban, 2021)
It is of no doubt that our country's COVID-19 vaccination exercise has, since July 2021, been extraordinary and commendable. To date, close to 40 million doses of COVID-19 vaccines have been administered with more than 17 million people having already received 2 doses. The population of Klang Valley, in particular, has currently received the highest number of doses in tandem with the primary goal of Operation Surge. While the previous emphasis was to intensify the vaccination exercise in states with the highest rates of infection and ICU utilization, it should now be shifted to neutralizing the looming dangers of monsoon season faced by the flood-prone states.